ANALISIS KESEDIAAN MEMBAYAR PADA OBJEK WISATA GUNUNG API PURBA NGLANGGERAN DI DAERAH ISTIMEWA YOGYAKARTA - BELLA SYAVIRA; UNGGUL PRIYADI (Universitas Bandar Lampung (UBL), 2022)
This study aims to identify the variables that affect the willingness to pay for environmental quality improvement in Nglanggeran Ancient Volcano. This study uses primary data with a total of 100 respondents. And the sample collection technique uses a combination of accidental sampling and purposive sampling using a contingent valuation method (CVM) approach. The analytical tool in this study is to use logistic binary regression on SPSS Version 21.0 for windows. The findings of this study indicate that the variables of age and number of dependents have a negative and significant effect on willingness to pay for improving environmental quality at the Nglanggeran Ancient Volcano tourism object. While the variables of education level, recreation costs, income, and frequency of visits have a positive and significant effect. The results of this investigation indicate that the value of Nagelkerke's R Square is 0.93 or 93%. Willingness to pay to improve the environmental quality of the Nglanggeran Ancient Volcano can be proven 93% influenced by education level, recreation costs, income, frequency of visits, age, and dependents, with 7% variance explained by factors outside the model.